2020
DOI: 10.3847/1538-4357/abb5b4
|View full text |Cite
|
Sign up to set email alerts
|

EvryFlare. III. Temperature Evolution and Habitability Impacts of Dozens of Superflares Observed Simultaneously by Evryscope and TESS

Abstract: Superflares may provide the dominant source of biologically relevant UV radiation to rocky habitable-zone M-dwarf planets (M-Earths), altering planetary atmospheres and conditions for surface life. The combined line and continuum flare emission has usually been approximated by a 9000 K blackbody. If superflares are hotter, then the UV emission may be 10 timeshigher than predicted from the optical. However, it is unknown for how long M-dwarf superflares reach temperatures above 9000 K. Only a handful of M-dwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 79 publications
8
88
0
Order By: Relevance
“…However, while these studies have shown that the optical spectrum of many flares can be broadly approximated with a 9000-10 000 K blackbody, the flare temperature has been observed to change both between and within individual flare events to values outside this range (e.g. Howard et al 2020a). We note that while this limits the use of a single temperature model, we currently cannot predict these changes in the flare temperature, preventing the use of more complex models.…”
Section: Flare Energymentioning
confidence: 79%
“…However, while these studies have shown that the optical spectrum of many flares can be broadly approximated with a 9000-10 000 K blackbody, the flare temperature has been observed to change both between and within individual flare events to values outside this range (e.g. Howard et al 2020a). We note that while this limits the use of a single temperature model, we currently cannot predict these changes in the flare temperature, preventing the use of more complex models.…”
Section: Flare Energymentioning
confidence: 79%
“…If the flux distribution in the flare corresponds to a blackbody with temperature higher than about 10,000 K, the true energies will be larger. Thus, Schmitt et al (2019) adopt a blackbody flux distribution corresponding to 12,000 K, while Froning et al (2019) and Howard et al (2020) use 40,000 K. From Table 3 the range in flare energy is 10 33.5 to 10 36 erg with a mean of 10 34.5 erg, but these may be just lower limits.…”
Section: Tess Early-type Flare Starsmentioning
confidence: 99%
“…34 Different emission lines and continua vary by different factors on all timescales, while connections between the flare energy and frequency distribution of white light flares (such as those observed with Kepler/K2 and T ESS) and UV flares remain poorly constrained by observation and theory. [35][36][37][38] Estimates of the EUV response of the Great AD Leo Flare of 1985 39 observed with the International Ultraviolet Explorer, IU E, indicate that the atmospheres of planets orbiting very active stars with frequent flares never achieve a steady state because the timescales for atmospheric recovery are much longer than the time between successive flares. 40 EU V E provided constraints on flare frequencies for a small sample of young, active stars, 41 Characterization of the EUV flare frequency and spectral variability on stellar evolutionary timescales requires (1) directly collecting EUV spectra over long enough temporal baselines to monitor variability and (2) a broad sample of stars with a range of masses and ages (activity levels, e.g., West et al 2015).…”
Section: Euv Evolution and Flaresmentioning
confidence: 99%